Design Thinking : A Creative Approach to Develop an Employee Experience Scale - Patil, Rajeshwari; Pandita, Priyanka; Waghmare, Ganesh (Prabandhan: Indian Journal of Management, 2023)
The study aimed to develop and empirically validate the construct of employee experience, representing an organization’s ability to manage the employee experience. Organizations that build and work on employee experience develop expertise in deploying resources and routines to understand, evaluate, and improve how they interact with their workforce across all contact points. A rigorous process was employed to identify, operationally define, evaluate, and validate various dimensions reflecting employee experience. The dimensions were developed and validated using design thinking as an approach — focusing on empathy to identify the gains and pains of employees in the education sector. The empirically validated 29-item measurement scale provided practitioners with an approach to evaluate and improve their organization’s employee experience quotient. It permits comparisons of individuals and organizations, enabling competitive benchmarking within and across industry sectors. Developing valid and reliable measurement scales is an essential first step in measuring the experience in an organization. The paper recommended a theoretical foundation for the employee experience construct and authenticated an equivalent measurement scale. The scale was developed prudently to accomplish the specificity required to undertake the meaningful expert-centric valuation. The developed scale permits future intellectual investigation through employee experience evaluations both inside and amongst organizations or sectors.